Plastics materials - Brydson, J. A. (Oxford ; Boston : Butterworth-Heinemann, 1999)
Provides an overview of the nature, manufacture, structure, properties, processing, and applications of commercially available plastics materials. This revised and updated edition adds new chapters on materials selection and special polymers, including biodegradable and electroconductive polymers and thermoplastic elastomers. In addition, many new plastics materials are added throughout and more information is included on testing methods and data.
The historical development of plastics materials; The chemical nature of plastics; States of aggregation in polymers; Relation of structure to thermal and mechanical properties; Relation of structure to chemical properties; Additives for plastics; Principles of the processing of plastics; Principles of product design; Polyethylene; Aliphatic polyolefins other than polyethylene, and diene rubbers; Vinyl chloride polymers; Fluorine-containing polymers; Poly (vinyl acetate) and its derivatives; Acrylic plastics; Plastics based on styrene; Miscellaneous vinyl thermoplastics; Polyamides and polyimides; Polycarbonates; Other thermoplastics containing p-phenylene groups; Cellulose plastics; Phenolic resins; Aminoplastics; Polyesters; Epoxide resins; Polyurethanes and polyisocyanurates; Furan resins; Silicones and other heat-resisting polymers; Miscellaneous plastics materials; Special functional polymers; Materials selection.
Includes bibliographical references and index.
Keywords: Plastics; Electronic books